2017
DOI: 10.1139/apnm-2017-0267
|View full text |Cite
|
Sign up to set email alerts
|

Compounds from Ilex paraguariensis extracts have antioxidant effects in the brains of rats subjected to chronic immobilization stress

Abstract: Immobilization induces oxidative damage to the brain. Ilex paraguariensis extracts (Mate) and their major natural compound, chlorogenic acid (CGA), exert protective effects against reactive oxygen species formation. Here, the effects of Mate and CGA on oxidative damage induced by chronic immobilization stress (CIS) in the cortex, hippocampus, and striatum were investigated. For CIS, animals were immobilized for 6 h every day for 21 consecutive days. Rats received Mate or CGA by intragastric gavage 30 min befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 46 publications
(44 reference statements)
1
9
0
1
Order By: Relevance
“…Although unpublished data of our group suggest variable redox effects in different organs of LAC‐1‐bearing mice, the current work did not show redox involvement of the identified bioavailable compounds as lipoperoxide‐modulating agents. The antioxidant capacity of IP has demonstrated to be neuroprotective under different conditions (Colpo et al, ; De Lima et al, ). In the case of lung cancer, additional deleterious responses are triggered in the brain and its cells, such as inflammation (Cittadini et al, ; Cittadini et al, ), which was controlled here.…”
Section: Discussionmentioning
confidence: 99%
“…Although unpublished data of our group suggest variable redox effects in different organs of LAC‐1‐bearing mice, the current work did not show redox involvement of the identified bioavailable compounds as lipoperoxide‐modulating agents. The antioxidant capacity of IP has demonstrated to be neuroprotective under different conditions (Colpo et al, ; De Lima et al, ). In the case of lung cancer, additional deleterious responses are triggered in the brain and its cells, such as inflammation (Cittadini et al, ; Cittadini et al, ), which was controlled here.…”
Section: Discussionmentioning
confidence: 99%
“…However, the consumption of Ilex paraguariensis by healthy individuals leads to increased GSH levels when compared with baseline values prior to its consumption (Boaventura et al, 2015). Yerba mate contains several bioactive compounds with redox‐modulating properties that act against ROS (Colpo et al, 2017). The same effect on GSH levels been observed in patients presenting with chronic diseases, such as diabetes mellitus Type II (Boaventura et al, 2013), dyslipidemia, and cardiovascular disease (Boaventura et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Mate was previously associated with lower PD risk in Argentina, and caffeine was considered the probable mediator of this effect (7). Previous studies have demonstrated a high content of antioxidants and substances with iron chelation properties in IP, which could elicit a potential protective effect on PD (8,9). In a recent study by Bernardi et al (10), they demonstrated that IP may have a strong neuroprotective activity on dopaminergic neurons, preventing their death with a dosedependent effect (10).…”
Section: Introductionmentioning
confidence: 98%